(untitled) (European Journal of Economics, Finance and Business Development, 2026)
This article examines the fair value measurement of investment property in accordance with International Accounting Standard (IAS) 40. Investment property represents an important category of assets that can significantly influence the financial position and performance of companies. The study analyzes the theoretical foundations of fair value measurement and its role in improving the transparency and reliability of financial reporting. Particular attention is paid to the advantages and challenges associated with the application of the fair value model in practice. The research also discusses common issues faced by companies in determining the fair value of investment property, including the lack of active markets, valuation subjectivity, and the availability of reliable market data. In addition, the paper considers the practical implications of fair value measurement for financial decision-making and financial reporting quality. Based on the analysis, several recommendations are proposed to improve the reliability and effectiveness of investment property valuation under IAS 40.